Relation between general throwing tests with a medicine ball and specific tests to evaluate throwing velocity with and without opposition in handball - Rivilla-Garcia, J.; Martinez, I.; Grande, I.; Sampedro Molinuevo, J. (Journal of Human Sport & Exercise, 2011)
The aim of the present study was to analyze the relationship among general throwing tests, with a medicine ball, and throwing velocity tests with and without opposition in different groups of handball players, thus analyzing the influence of technique and decision making in specific throwing capacity. To do this, ninety-four handball players of different competitive levels, age groups and playing positions were tested in four throws of progressive specificity: a) throwing with a heavy medicine ball (THMB); b) throwing with a light medicine ball (TLMB); c) throwing velocity (VS); and d) throwing velocity with opposition (VO). The correlational study, using Pearson's correlation coefficient, was found to be significant (p < 0.01) in the relations among the different tests in the whole sample and all groups. The data indicated not very high correlations between the THMB and the other tests, especially with the VO in the over 18 senior players (r=0.404**). Correlation values for TLMB-VS were very high in general (r=0.904**) and in all groups. By contrast, the correlation between the throwing tests was not high, especially in the under 18 players (r=0.621**), backcourt players (r=0.632**) and central players (r=0.594**). The data lead to the conclusion that the general test has limited utility for assessing specific throwing capacity; that TLMB adequately predicts VS; and that opposition has a significant influence on specific throwing speed.